2008
DOI: 10.4081/ijas.2008.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofLactobacillus acidophilusD2/CSL on laying hen performance

Abstract: In order to evaluate the effects of dietary addition of probiotic strain Lactobacillus acidophilus D2/CSL on hen performance and egg quality, 160 commercial Hy-Line Brown pullets, 17 weeks old, were divided in control group (C) (N=80) and treated group (T) (N=80), with 4 alternate replicates of 20 animals each per group. C was fed with a "standard diet", whereas the T group received the same diet with an inclusion of 1x10 9 CFU kg -1 of Lactobacillus acidophilus D2/CSL (freeze dried cells). The experimental tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 34 publications
1
28
0
2
Order By: Relevance
“…Previous investigators have revealed that addition of probiotics to the feed of poultry (broilers and laying hens) has beneficial effects on growth performance and egg production. In laying hens, Gallazzi et al (2008) indicated that egg production and FCR were significantly improved when hens were treated with probiotic strain Lactobacillus acidophilus D2/CSL. Similar results were found by Li et al (2005) when a Bacillus subtilis culture was used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have revealed that addition of probiotics to the feed of poultry (broilers and laying hens) has beneficial effects on growth performance and egg production. In laying hens, Gallazzi et al (2008) indicated that egg production and FCR were significantly improved when hens were treated with probiotic strain Lactobacillus acidophilus D2/CSL. Similar results were found by Li et al (2005) when a Bacillus subtilis culture was used.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic supplementation has been shown to improve the performance and efficiency of nutrient use in broilers [38,[44][45][46][47][48] and in laying hens and pullets [49][50][51][52][53][54][55][56]. This improvement is presumed to be a result of bacterial antagonism, competition for colonization sites, competition for nutrients, a reduction in the production of toxic compounds, or modulation of the immune system [13].…”
Section: Probiotics: Product Development and Purported Benefitsmentioning
confidence: 99%
“…Some investigations on probiotics with laying hens indicated positive responses to dietary supplementation (Li et al, 2006;Kurtoglu et al, 2004). In addition, Gallazzi et al (2008) and observed significant improvements in egg production in layers receiving probiotics. Prebiotics are nondigestible carbohydrates; many of these carbohydrates are short chains of monosaccharides, called oligosaccharides.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous studies in humans and animals have been conducted to assess the ability of probiotics to change the type and number of the microflora in the digestive tract (Gibson and Fuller, 2000). Some investigations on probiotics with laying hens indicated positive responses to dietary supplementation (Li et al, 2006;Kurtoglu et al, 2004). In addition, Gallazzi et al (2008) and observed significant improvements in egg production in layers receiving probiotics.…”
Section: Introductionmentioning
confidence: 99%